1347 Systematic review of the effectiveness of advocacy interventions for adult victims of domestic violence within an emergency department setting. Issue 12 (22nd November 2022) - Basheer, Mohamed Bushry; Bell, Rachel; Boyle, Adrian
Abstract : Aims, Objectives and Background: Advocacy interventions for survivors of domestic violence is well established and supported by evidence in some community and healthcare settings. Survivors of domestic violence identified in emergency departments have important differences and it is not clear whether evidence can be applied to this population. Therefore, we conducted an inclusive systematic review of controlled studies evaluating the effectiveness of advocacy workers for adult survivors identified in emergency departments. Method and Design: We included studies that reported primary research studies evaluating the effectiveness of advocacy workers in supporting survivors of domestic abuse conducted in emergency departments. We excluded studies that reported screening trials, interventions to increase identification of abuse by healthcare staff, studies conducted on children and studies that weren't reported in English. The search for studies was done via the following online databases from their start dates till February 2022: PubMed/MEDLINE, Cochrane Library, CINAHL/Ebsco, EMBASE and PsycINFO. We anticipated that there would be few high quality double-blinded RCTs and aimed to include before and after studies. Results and Conclusion: We only found one randomised control trial that met our inclusion criteria, and several observational studies which were judged as too weak for inclusion. We found a non-peer reviewed study done as part of a dissertation by a UK emergency consultant, as well as an unpublished randomised controlled trial carried out as part of a PhD thesis. None of the studies we found reported harm from advocacy interventions. The cost effectiveness is uncertain, but likely to be beneficial. We are able to make a weak recommendation that advocacy interventions are likely to helpful, unlikely to be harmful but are of uncertain cost effectiveness. Future research should define meaning outcomes and controlled trials evaluating referral to advocacy are justified. Survivors of domestic violence who present to emergency departments are likely to benefit from referral to advocacy workers.